2008
DOI: 10.1309/ujjth4hfepwaq78q
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Genome Deletion Aids in the Identification of False- and True-Negative Prostate Needle Core Biopsy Specimens

Abstract: We report the usefulness of a 3.4-kb mitochondrial genome deletion (3.4 mtdelta) for molecular definition of benign, malignant, and proximal to malignant (PTM) prostate needle biopsy specimens. The 3.4 mtdelta was identified through long-extension polymerase chain reaction (PCR) analysis of frozen prostate cancer samples. A quantitative PCR assay was developed to measure the levels of the 3.4 mtdelta in clinical samples. For normalization, amplifications of a nuclear target and total mitochondrial DNA were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 16 publications
1
40
1
Order By: Relevance
“…Because the Cts of our previous assays were generally high, 9 we optimized the assay to improve efficiency and specificity. We redesigned the primers for the deletion and this dropped the annealing temperature from 66 to 64.4 1C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the Cts of our previous assays were generally high, 9 we optimized the assay to improve efficiency and specificity. We redesigned the primers for the deletion and this dropped the annealing temperature from 66 to 64.4 1C.…”
Section: Resultsmentioning
confidence: 99%
“…9 This could resolve negative prostate biopsies into true-and falsenegative categories. However, of the 96 patients in the validation study that provided proximal biopsy samples, only 48 had accompanying malignant biopsy cores for comparative analysis of test performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutations in mitochondrial DNA of histologically normal tissue may indicate a ‘cancerization’ or field effect similar to that of methylation studies. [94, 95] In the initial reports of this assay in 101 patients with an initially negative biopsy who underwent repeat biopsy within 1 year demonstrated sensitivity, specificity, and negative predictive value of 84%, 54%, and 91%, respectively. [96] This study demonstrated that the assay was able to predict the presence of a missed tumor in 17 out of 20 men a year before diagnosis.…”
Section: Currently Available Testsmentioning
confidence: 99%
“…An early study involving a cohort of 183 men including those with benign, malignant or proximaltomalignant biopsy samples, generated a remarkable AUC of 0.87 using this test in the validation phase of this study. 58 In a followup study of 101 patients undergoing repeat biopsy procedures, 20 were found to have prostate cancer within 1 year of the initial biopsy; analysis of biopsy samples for prostate cancer using the PCMT generated a sensitivity and specificity of 84% and 54%, respectively, (AUC 0.75) and a negative predictive value of 91%. 59 Larger validation studies are required before the widespread use of this assay can be recommended.…”
Section: Key Pointsmentioning
confidence: 99%